The influence of diet on gut microbiome and body mass dynamics in a capital-breeding migratory bird - Isabelle Jones; Kirsty Marsh; Tess M. Handby; Kevin Hopkins; Julia Slezacek; Stuart Bearhop; Xavier A. Harrison (PeerJ, 2023)
Gut-associated microbial communities are known to play a vital role in the health and fitness of their hosts. Though studies investigating the factors associated with among-individual variation in microbiome structure in wild animal species are increasing, knowledge of this variation at the individual level is scarce, despite the clear link between microbiome and nutritional status uncovered in humans and model organisms. Here, we combine detailed observational data on life history and foraging preference with 16S rRNA profiling of the faecal microbiome to investigate the relationship between diet, microbiome stability and rates of body mass gain in a migratory capital-breeding bird, the light-bellied Brent goose (Branta bernicla hrota). Our findings suggest that generalist feeders have microbiomes that are intermediate in diversity and composition between two foraging specialisms, and also show higher within-individual plasticity. We also suggest a link between foraging phenotype and the rates of mass gain during the spring staging of a capital breeder. This study offers rare insight into individual-level temporal dynamics of the gut microbiome of a wild host. Further work is needed to uncover the functional link between individual dietary choices, gut microbiome structure and stability, and the implications this has for the reproductive success of this capital breeder.